Proceedings of the 15th International Conference on Artificial Intelligence and Law 2015
DOI: 10.1145/2746090.2746108
|View full text |Cite
|
Sign up to set email alerts
|

The case law of the Italian constitutional court, its power laws, and the web of scholarly opinions

Abstract: The paper examines the citation network of the via incidentale rulings of the Italian Constitutional Court ("ICC"), vis-à-vis the web of scholarly opinions, comments, and annotations, devoted to such cases. The aim is to deepen the notion of legal relevance. On the one hand, a remarkable number of cases that are considerably discussed by experts, are neither hubs nor authorities in the ICC citation network. On the other hand, cases that are relevant in the ICC citation network are scarcely debated, or even ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…In particular, the identification rate values of the HITS authority score are 0.143 (APS), 0.116 (HEP), and 0.054 (PAT). 7 The poor performance of HITS here is very different from this algorithm being praised in the line of research on court decision citation networks (see Fowler and Jeon (2008); Agnoloni and Pagallo (2015) and the references therein). One possible reason for this difference is that in science, few would agree that a citation from a well-referenced but little cited review paper is more indicative of the target paper's impact than a citation from a high-impact paper with few references (as HITS authority score would assume).…”
Section: Metric Evaluation Using Identification Ratementioning
confidence: 93%
“…In particular, the identification rate values of the HITS authority score are 0.143 (APS), 0.116 (HEP), and 0.054 (PAT). 7 The poor performance of HITS here is very different from this algorithm being praised in the line of research on court decision citation networks (see Fowler and Jeon (2008); Agnoloni and Pagallo (2015) and the references therein). One possible reason for this difference is that in science, few would agree that a citation from a well-referenced but little cited review paper is more indicative of the target paper's impact than a citation from a high-impact paper with few references (as HITS authority score would assume).…”
Section: Metric Evaluation Using Identification Ratementioning
confidence: 93%
“…Véase Carmichael y otros (2017: 244): «Overall, the results agree with prior work that showed that authorities [an eigenvectorbased vertex centrality metric] predicted future citations better than in-degree». y para estudiar otras jurisdicciones, como Canadá, India, Italia, la Corte Europea de Justicia o la Unión Europea (Neale, 2013;Jacob, 2014;Koniaris, Anagnostopoulos y Vassiliou, 2014;Minocha, Singh y Srivastava, 2015;Agnoloni y Pagallo, 2015). Según Cross y otros (2010: 491), «esta área de investigación presenta la frontera más prometedora para el futuro de la investigación empírica sobre la toma de decisiones judiciales, y proveerá nuevos entendimientos sobre el desarrollo del derecho».…”
Section: Metodologíaunclassified
“…Subsequently, we have constructed eleven chains of decisions (connected to one another by a citation) leading to these five decisions, again paying attention to their indegree. We theorize that the decisions with higher indegree centrality as well as decisions with higher authority score will be cited in situations seeking a case-law argument for either procedural issue, or an issue of a more general nature, or an issue of principle, while the decisions with low indegree centrality or low authority score will be cited 1 This paper is a part of a project titled "Judikatura, nebo precedens: Podobnost citovaných rozhodnutí při citacích judikatury" (Project No. MUNI/A/0952/2019).…”
Section: Exploring the Relation Between The Indegree Centrality And Authority Score Of A Decision And The Reason For Which It Was Cited: mentioning
confidence: 99%
“…The question of whether or not do continental courts' decisions have any normative, or precedential, value has long been a part of legal discussions, attracting attention from numerous legal scholars. 2 Recently, this question has been given a more quantitative attention, employing network analysis to use citations to past decisions as a tool to determine the courts' actual practice in this matter. 3 Empirical data-driven research on theoretical legal concepts as well as various legal practices is one of the directions legal informatics follows recently.…”
Section: Introductionmentioning
confidence: 99%